2012
DOI: 10.1210/jc.2011-1769
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor Variants and Response to Pegvisomant in Monotherapy or in Combination with Somatostatin Analogs in Acromegalic Patients: A Multicenter Study

Abstract: This study did not confirm a better response of d3GHR to PEG-V treatment in acromegaly. Other studies are needed to determine whether deviation from Hardy-Weinberg equilibrium may indicate an association of d3GHR genotype with poor response to usual treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
1
31
1
3
Order By: Relevance
“…However, Filopanti and cols. (27) in a larger multicenter study (111 patients) did not find a difference in the response rates to pegvisomant treatment between those patients presenting d3GHR or the flGHR. Additionally, Franck and cols.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, Filopanti and cols. (27) in a larger multicenter study (111 patients) did not find a difference in the response rates to pegvisomant treatment between those patients presenting d3GHR or the flGHR. Additionally, Franck and cols.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, some studies evaluated the GHR polymorphisms as a possible cause of a lower response to the drug, with conflicting results regarding whether patients who present the exon-3 deleted GHR (d3GHR) had a better response to pegvisomant (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…To date, findings from 17 studies, which are summarized in Table 4, have not been consistent and the importance of the d3-GHR polymorphism in acromegaly management remains highly controversial (55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71). The number of patients with acromegaly examined varied from 19 to 186 among the reported series, with the prevalence of heterozygous d3/fl-GHR ranging from 13.3% to 57% and of d3-GHR homozygous from 0% to 22%.…”
Section: Ghr Polymorphism In Acromegalymentioning
confidence: 99%
“…Indeed, two studies reported that the required PEGV dose for normalization of IGF1 levels was significantly lower in acromegaly patients with a d3-GHR genotype (5,6). A later study, however, did not observe a better response of d3-GHR carriers during monotherapy PEGV nor during combination treatment with PEGV and somatostatin analogues (10). These inconsistent findings indicate that larger cohorts of acromegaly patients are needed to investigate whether the response to PEGV differs between d3-GHR and fl-GHR genotypes.…”
Section: Introductionmentioning
confidence: 98%
“…About half of the population is homozygous for the full-length GHR (fl-GHR), 30-40% is heterozygous for d3-GHR and 10-20% is homozygous for this deletion (7,8,9). It has been reported that the d3-GHR polymorphism shows a comparable distribution between different cohorts of acromegalic patients (6,10,11,12). Multiple studies show that the fl-GHR and d3-GHR have comparable binding properties, and that internalization of fl-GHR is as effective as d3-GHR (13,14,15).…”
Section: Introductionmentioning
confidence: 99%